Silence as Structural Presence: A Theoretical Exploration of Ivan Ikićʹs Film “Oaza” [Oasis] within a Cinematic Framing of Noam Chomsky’s Minimalist Program - Jakab, Edit (Slavica, 2026)
This study proposes a formal-analytical reading of Ivan Ikić’s Oaza [Oasis] (2020) within an interdisciplinary framework combining film theory and Noam Chomsky’s Minimalist Program. Drawing on core Minimalist concepts – such as the distinction between Phonological Form (PF) and Logical Form (LF), economy of derivation, and the copy theory of movement – the article argues that cinematic silence in Oaza is not absence, but a structurally licensed form of non-externalization. In this sense, silence functions analogously to syntactic traces: elements that lack phonological realization yet remain interpretively active. Focusing on the interrogation scene and the final sequence of the film, the analysis demonstrates how the suspension of speech and the restriction of expressive means shift interpretive responsibility onto the viewer. Meaning emerges not through explicit articulation, but through structured absence and constrained access. The film thus operates as a derivational system in which omission is not a deficit but a condition of interpretation, governed by principles of economy and interface interaction.